(untitled) (Research, Society and Development, 2021)
This study characterized the topography osseointegrated implants (cp-Ti) with machined surface (MS), laser beam surface (LS) and laser beam surface followed by deposition of sodium silicate (SS) by means SEM-EDX, roughness measurements, cross-sectional roughness, contact angle, X-ray diffraction (XRD) and laser confocal optical perfilometry. The SEM of MS showed smooth surface, contaminated with machining residues, while LS and SS rough surfaces with a more regular and homogeneous morphological pattern. The EDX showed Ti peaks for MS and Ti and oxygen for LS and SS. The mean roughness values of LS and SS were statistically higher (p <0.05) than MS. The contact angle of LS and SS was 0º. The XRD of MS showed only Ti peaks, while LS and SS showed the presence of oxides and nitrides and presence of sodium silicate. The surface treatment performed in the LS and SS promoted important modifications in the topography and physical-chemical properties.